A Kalecki fable on debt and the monetary transmission mechanism. (April 2016) - Toporowski, Jan
Abstract : Kalecki explained debt resolution by means of a fable about monetary circulation between mutually indebted individuals. This note explains the context and some of the theoretical implications of the fable. These point to an asymmetry in monetary policy in which excessively tight monetary policy may restrict economic activity and force the resort to informal debt.